Perbedaan Penyembuhan Luka Bakar Derajat II antara Pemberian Topikal Ekstrak Sel Punca Mesenkimal Wharton’s Jelly Tali Pusat Manusia dan Moist Exposed Burn Oitment (MEBO) pada Tikus Putih Jantan (Rattus Norvegicus) Galur Sparague Dawley - Eka Lestari; Evi Kurniawati; Fitria Saftarina (CV. Jasa Sukses Abadi, 2020)
Abstract Moist Exposed Burn Ointment (MEBO) is an ointment which can accelerate burn healing. Wharton's jelly mesenchymal stem cell (WJMSc) extract in human umbilical cord has the ability to potentially assist the burns healing process. This research was a laboratory experimental study with the use of 27 white rat induced with second degree burns and was divided into a control group (K1), Moist Exposed Burn Ointment (MEBO) group (P1) and WJMSc (P2) group. Observation of burn healing rate used healing time and burn diameter was conducted for 28 days. Data were analyzed using One way ANOVA and Kruskal wallis statistic test with 5% of α value. Average burn healing rate of K1 group: 26,78 days, P1: 24,56 days, P2: 19,67 days with the result of burn healing rate data analyzed test is p:0,005. Differences in burn diameter occurred on day 8, 12, 16, 20 and 24 on the ploriferation and remodeling stage with the result of burn diameter data analyzed test is p<0,05. Conclusion: There was a significant difference on the speed of burn healing and burn diameter between treatment group with p: 0,001. WJMSc is the fastest therapy and the largest diameter cutback.